Multiple Glutathione S-Transferase Genes in Heortia vitessoides (Lepidoptera: Crambidae): Identification and Expression Patterns. Issue 3 (14th June 2018) - Cheng, Jie; Wang, Chun-Yan; Lyu, Zi-Hao; Lin, Tong
Abstract: To elucidate the role of glutathione S-transferases (GSTs) in Heortia vitessoides Moore (Lepidoptera: Crambidae), one of the most destructive defoliating pests in Aquilaria sinensis (Lour.) Gilg (Thymelaeaceae) forests, 16 GST cDNAs were identified in the transcriptome of adult H. vitessoides . All cDNAs included a complete open reading frame and were designated HvGSTd1 – HvGSTu2 . A phylogenetic analysis showed that the 16 HvGSTs were classified into seven different cytosolic classes; three in delta, two in epsilon, three in omega, three in sigma, one in theta, two in zeta, and two in unclassified. The expression patterns of these HvGSTs in various larval and adult tissues, following exposure to half the lethal concentrations (LC50 s) of chlorantraniliprole and beta-cypermethrin, were determined using real-time quantitative polymerase chain reaction (RT-qPCR). The expression levels of the 16 HvGSTs were found to differ among various larval and adult tissues. Furthermore, the RT-qPCR confirmed that the transcription levels of nine ( HvGSTd1, HvGSTd3, HvGSTe2, HvGSTe3, HvGSTo3, HvGSTs1, HvGSTs3, HvGSTu1, and HvGSTu2 ) and six ( HvGSTd1, HvGSTd3, HvGSTe2, HvGSTo2, HvGSTs1, and HvGSTu1 ) HvGST genes were significantly higher in the fourth-instar larvae following exposure to the insecticides chlorantraniliprole and beta-cypermethrin, respectively. These genes are potential candidates involved in the detoxification of these two insecticides. Further studies utilizing the RNA interference approach are required to enhance our understanding of the functions of these genes in this forest pest.